Surgical training in ophthalmology: Role of EyeSi in the era of simulation-based learning - Abdul Sami Memon; Sehrish Nizar Ali Momin; Muhammad Bilal Malik; Pir Salim Mahar (Journal of the Pakistan Medical Association, 2022)
Recent advancements in surgical training methods have escalated the need for simulators. The EyeSi simulation has played a major role in Ophthalmology training by providing opportunity to the novice residents to grasp the surgical steps of the procedure and master the skill by repeated attempts. Participants were as-sessed on single level of cataract module and their consecutive scores were assessed with each attempt. It was found that repetitive practice on simulator can help develop proficiency in the desired steps that can ultimately prepare the surgical trainees for real life surgery. Continuous...